STRUKTUR WACANA IKLAN PERDUKUNAN DI INDONESIA - Ashari Hidayat (Sunan Kalijaga State Islamic University Yogyakarta, 2009)
The research aims describe the discourse components and patterns structure of perdukunan (a person who can make contact with the world of spirit or the world of shamanism, medicine man, healer, exorcist, etc) advertisement. The objective of this research is to analyze the discourse perdukunan advertisement. In addition, the descriptive method combined with sociolinguistic study approach use in this research. Three stage of descriptive method are data collecting, data analysis, and analysis explanation. Data recourse take from Posmo tabloid. The data are described by the theory of discourse analysis and situational aspects on the theory sociolinguistics. Base on the elaboration and the explanation of data, it is found that perdukunan advertisement component and pattern varies. Perdukunan advertisement discourse component consists of problems elements, resolutions of those elements, and the reinforcements of element. The discourse pattern of perdukunan advertisement consists of introduction, body and closing. Those three parts comprised both main components and supporting component. The main component was the information which proved the information of O1 identity, problem and resolution. The supporting component was the proposition which confirmed or supported the information of main components. Those which included in the supporting components were testimony, guarantee and suggestion.